The effects of social network sites on brand awareness and attitude - Souto, D.; Salgueiro, M.F.; Rita, P. (Proceedings of the 2nd International Conference on Contemporary Marketing Issues, ICCMI 2014, 2014)
Brands are increasingly targeting Social Network Sites´ (SNS) massive audiences and incorporating the new media channel in their communication plans. Despite its growing adoption, few research efforts have been devoted to evaluate SNS´ concrete consequences for the brands. In the current study we evaluate SNS´ effects on generating brand awareness and positive brand attitude, two important measures on delivering efficient communication efforts. An online quantitative survey with brand page users of leading brands at Facebook was implemented. Structural equation modeling was used for model estimation. Results have verified a significant, positive and direct impact of brand page participation on brand awareness. Brand attitude also substantially benefits from brand page participation, but this relationship is mediated by brand awareness. Related implications are discussed